Collision tumor of metastatic carcinoma and lymphoma in the bone marrow: Report of an extremely rare and interesting case and review of the literature (Indian Journal of Case Reports, 2017)
Collision tumors are composed of two or more histologically distinct tumor components occurring at the same anatomic location. Collision tumors composed of metastatic carcinoma and lymphoma in the bone marrow is an extremely rare occurrence which is not yet reported in literature. We are reporting a case of 61 year old male patient diagnosed as grey zone lymphoma in the oral cavity (B cell lymphoma unclassifiable with features intermediate between DLBCL and Burkitt lymphoma) and bone marrow showing collision tumor composed of metastatic carcinoma and lymphoma.